1963
DOI: 10.1182/blood.v22.4.416.416
|View full text |Cite
|
Sign up to set email alerts
|

The Gastrointestinal Tract and Iron Absorption

Abstract: 1. Using Fe59 and whole body counting, various aspects of gastrointestinal absorption of iron salts were studied in normal, iron-loaded, and iron-deficient rats. 2. Following a single intragastric dose of iron, peak small intestinal uptake was observed by 30 to 60 minutes with subsequent gradual loss over 24-hour period. 3. Iron absorption showed two phases, an initial period of rapid absorption lasting up to 2 hours during which 60 to 80 per cent of total absorption into carcass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

1967
1967
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(26 citation statements)
references
References 13 publications
2
22
0
2
Order By: Relevance
“…Kinetic studies of iron absorption have shown that iron is absorbed through the mucosa in two phases: A rapid phase starts within seconds after iron reaches the mucosal surface and lasts about 30-60 minutes; a slower phase continues for many hours thereafter [93,94]. Further, the absorption process can be regarded anatomically as a two-step transport mechanism: mucosal uptake of iron from the intestinal lumen and mucosal transfer of iron into the body.…”
Section: Mucosal Factorsmentioning
confidence: 99%
“…Kinetic studies of iron absorption have shown that iron is absorbed through the mucosa in two phases: A rapid phase starts within seconds after iron reaches the mucosal surface and lasts about 30-60 minutes; a slower phase continues for many hours thereafter [93,94]. Further, the absorption process can be regarded anatomically as a two-step transport mechanism: mucosal uptake of iron from the intestinal lumen and mucosal transfer of iron into the body.…”
Section: Mucosal Factorsmentioning
confidence: 99%
“…It is known that previous exposure to iron impairs the subsequent passage of iron through the duodenal mucosal cell Schachter, 1962, 1964;. Such exposure to iron appears to inhibit the passage of iron through a rapid transit, enzyme-mediated pathway for iron absorption (Manis and Schachter, 1964; and subsequent absorption is slow or negligible (Wheby and Crosby, 1963;Manis and Schachter, 1964;Wheby, Jones and Crosby, 1964). Some at least of this storage iron appears to be in the form of ferritin (Manis and Schachter, 1964;Charlton et at., 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Iron which is destined to pass across the small intestinal mucosa and into the circulating plasma does so very rapidly after its uptake by the epithelial cells. Hallberg & Solve11 (1960) have shown that after a single oral dose of iron most of the absorbed portion had entered the blood stream within 2 h. Wheby & Crosby (1963) have shown a similar rapidity of absorption after the intragastric administration of iron in rats. When labelled iron was injected directly into a loop of small intestine there was virtually no time lag between the injection and the appearance of labelled iron in the circulating blood (Charley et a!, 1963).…”
Section: The Intestinal Epithelial Cellmentioning
confidence: 95%
“…Later experiments showed that mucosal uptake of iron decreased very little from the pylorus to the terminal ileum but serosal transfer was largely limited to the duodenum. Wheby & Crosby (1963) found that after a gastric dose of labelled iron the maximum uptake was in the first quarter of the small intestine. Uptake was greatest in iron deficient animals and least in iron loaded animals.…”
Section: The Intestinal Epithelial Cellmentioning
confidence: 97%